The Two Forms of Lysine Decarboxylase; Kinetics and Effect of Expression in Relation to Acid Tolerance Response in E. coli - Arunachalam1, Hannah Priyanka1,3 and Karunakaran Indulekha1,4, Gokulnath Krithika1,2*, Jothi (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Lysine decarboxylase has gained importance recently due to its involvement in acid tolerance response in some pathogenic bacteria. Two forms of the enzyme exist. One, CadA, is part of an operon and is induced by changes in external pH. The other form, Ldc, is constitutively expressed. The differences between the two enzymes have not been understood fully. CadA has been studied more extensively whereas Ldc has not received much attention. The enzymes Ldc and CadA were purified individually using Ni-affinity chromatography from over expressing clones and it was found that their Km for lysine were 0.84mM and 0.27mM respectively. Their velocities, Vmax, were 27.21nmol cadaverine/min/µg of enzyme, and 8.148nmol cadaverine/min/µg of enzyme respectively. Epsilon aminocaproic acid (EACA), benserazide, carbidopa and voveran were added to the enzyme. Voveran inhibited only the inducible form of the enzyme. The assay of activity of each of these enzymes during growth of E.coli suggests that the two forms of the enzyme might be expressed at various phases of growth. This might be the probable reason for the presence of two enzymes which catalyse essentially the same reaction.